Cotonou's next breath: Particulate matter monitoring and capturing - Basile Kounouhewa; Gabin Koto N'Gobi; Hervé Houngue; Lothar Müller; Michael Wirtz; Selçuk Yurtsever-Kneer; Helga Fink; Aron Kneer; Stéphan Barbe (Scientific African, 2020)
Air pollution due to high concentrations of small particles is a severe issue in West Africa. In this regard, the international scientific team of the DACCIWA project (Dynamics-Aerosol-Chemistry-Cloud-Interactions In West Africa) recently published the policy relevant findings of this action and clearly claimed the need for long-term and reliable measurements of meteorological data and particulate matter concentrations in South West Africa. This short communication describes the progress achieved in the frame of Beninese-German scientific mission. An experimental setup for the long-term and continuous monitoring of meteorological data and particulate matter pollution was developed and installed in Cotonou (Benin). In addition, two pilot scale particle separators (each 2 m × 2 m) was developed, constructed and taken in to operation. The measured particulate matter concentrations clearly exceed the limits set by the World Health Organization and the European Union.